MRI Characteristics of Pediatric Renal Tumors: A SIOP‐RTSG Radiology Panel Delphi Study. Issue 2 (6th August 2021) - van der Beek, Justine N.; Watson, Tom A.; Nievelstein, Rutger A.J.; Brisse, Hervé J.; Morosi, Carlo; Lederman, Henrique M.; Coma, Ana; Gavra, Maria M.; Vult von Steyern, Kristina; Lakatos, Karoly; Breysem, Luc; Varga, Edit; et al.
Abstract : Background: The SIOP‐Renal Tumor Study Group (RTSG) does not advocate invasive procedures to determine histology before the start of therapy. This may induce misdiagnosis‐based treatment initiation, but only for a relatively small percentage of approximately 10% of non‐Wilms tumors (non‐WTs). MRI could be useful for reducing misdiagnosis, but there is no global consensus on differentiating characteristics. Purpose: To identify MRI characteristics that may be used for discrimination of newly diagnosed pediatric renal tumors. Study Type: Consensus process using a Delphi method. Population: Not applicable. Field Strength/Sequence: Abdominal MRI including T1‐ and T2‐weighted imaging, contrast‐enhanced MRI, and diffusion‐weighted imaging at 1.5 or 3 T. Assessment: Twenty‐three radiologists from the SIOP‐RTSG radiology panel with ≥5 years of experience in MRI of pediatric renal tumors and/or who had assessed ≥50 MRI scans of pediatric renal tumors in the past 5 years identified potentially discriminatory characteristics in the first questionnaire. These characteristics were scored in the subsequent second round, consisting of 5‐point Likert scales, ranking‐ and multiple choice questions. Statistical Tests: The cut‐off value for consensus and agreement among the majority was ≥75% and ≥60%, respectively, with a median of ≥4 on the Likert scale. Results: Consensus on specific characteristics mainly concerned the discrimination between WTs and non‐WTs, and WTs and nephrogenic rest(s) (NR)/nephroblastomatosis. The presence of bilateral lesions (75.0%) and NR/nephroblastomatosis (65.0%) were MRI characteristics indicated as specific for the diagnosis of a WT, and 91.3% of the participants agreed that MRI is useful to distinguish NR/nephroblastomatosis from WT. Furthermore, all participants agreed that age influenced their prediction in the discrimination of pediatric renal tumors. Data Conclusion: Although the discrimination of pediatric renal tumors based on MRI remains challenging, this study identified some specific characteristics for tumor subtypes, based on the shared opinion of experts. These results may guide future validation studies and innovative efforts. Level of Evidence : 3 Technical Efficacy Stage : 3